Clinical and immunological parameters of Newcastle disease vaccination in Chinese goose (Anser cygnoides) - Campioni, Josie Maria [UNESP] (2008)
Clinical and immunological parameters of vaccinated Chinese goose against Newcastle disease were evaluated. One hundred and twenty birds were distributed into four different experimental groups, vaccinated or not against Newcastle disease (ND): G1 (Ulster 2C strain), G2 (B1 strain), G3 (LaSota strain) and G4 (nonvaccinated -control).The immune response was evaluated by the HI test. The vaccinations of Chinese geese with NDV Ulster 2C, B1 and LaSota strains did not cause any clinical signs associated with post-vaccinal reactions and were similar in the humoral immune response stimulus (HI). © Asian Network for Scientific Information, 2008.